Foundations of comparative politics - Clark, William Roberts 1962-; Golder, Matt; Golder, Sona Nadenichek (Thousand Oaks, California CQ Press/SAGE, 2019)
"Adapted from the groundbreaking Principles of Comparative Politics, now in its third edition, Foundations of Comparative Politics presents a scientific approach to the rich world of comparative inquiry, research, and scholarship, providing students a guide to cross-national comparison and why it matters to them. Foundations introduces students to the key questions in comparative politics using tools such as decision, social choice, and game theory to help them understand clearly why some explanations for political phenomena are stronger than others. Such an approach more closely replicates what comparative scholars do: constructing and testing theories on political phenomena, over basic memorization of country-specific facts - to explain, rather than describe. Through this approach, students gain invaluable real-world skills in critical thinking and empirical analysis that they will carry with them long after the course is over"-- Provided by publisher.
What is science? -- What is politics? -- The origins of the modern state -- The economic determinants of democracy and dictatorship -- The cultural determinants of democracy and dictatorship -- Democratic transitions -- Varieties of dictatorship -- Problems with group decision making -- Parliamentary, presidential, and semi-presidential democracies -- Elections and electoral systems -- Social cleavages and party systems -- Institutional veto players -- Consequences of democratic institutions.
Prof. Mae Claire Jabines (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
Keywords: Comparative government; Democracy